EFFECTIVENESS OF DOUBLE LUMEN CATHETER WOUND CARE USING 0.9% NaCL, 7.5% CHLORHEXIDINE, 15% CETRIMIDE ON DOUBLE LUMEN CATHETER INFECTION IN REGULAR HEMODIALYSIS PATIENTS - Heru Firman Andita; Zainal Abidin; Nur Hamim (Nurse and Health)
Background: The high incidence of double lumen catheter infections in Hemodialysis patients requires a solution including wound care using the antiseptic chlorhexidine 7.5% and cetrimide 15%.